Survival of Foodborne Pathogens on Berries - Mary Palumbo; Linda J. Harris; Michelle D. Danyluk (EDIS, 2014)
Fresh and frozen berries are popular foods. When berries are picked for fresh consumption, they are usually packed directly without washing because they are highly perishable. There is typically no “kill step” that would eliminate pathogens on fresh or frozen berries. Foodborne illness outbreaks have been associated with the consumption of fresh or frozen berries that were contaminated with pathogenic viruses, parasites, or bacteria. Contamination can occur before or during harvest or during final preparation. This 11-page fact sheet was written by Mary Palumbo, Linda J. Harris, and Michelle D. Danyluk, and published by the UF Department of Food Science and Human Nutrition, November 2013.